The formation of citizens: the pediatrician's role - Dioclécio Campos Júnior (Elsevier, 2016)
ABSTRACT Objective: This review article aims to define the fundamental role of the pediatrician in the formation of citizens in the 21st century. Source of data: Significant bibliographical contributions produced by neuroscience, ecology, and epigenetics in the early childhood scenario. Synthesis of data: Many diseases that impair the lives of adults result from severe and often uncontrollable disorders that occur in early childhood, an irreplaceable period for the safe construction of the human brain, personality, and intelligence. There is noteworthy scientific evidence that has become unquestionable, according to which abuse and neglect and other forms of violence to which children are exposed during the the course of their lives, are the genesis of many physical ailments and other mental diseases, including depressive morbidity and schizophrenia. Conversely, it is also emphasized that healthy practices such as reading and listening to/playing music are able to intensively contribute to the exercise of cognitive capacity inherent to this period of life, as a prerequisite for the acquisition of learning indispensable to the high educational performance during the schooling period. Conclusion: In the light of the disclosed scientific evidence, the pediatrician emerges as the most differentiated professional to provide preventive and curative care indispensable to the skilled formation of a healthy citizen.